Lateral suppressor and Goblet act in hierarchical order to regulate ectopic meristem formation at the base of tomato leaflets. (March 2015) - Rossmann, Susanne; Kohlen, Wouter; Hasson, Alice; Theres, Klaus
Summary In seed plants, new axes of growth are established by the formation of meristems, groups of pluripotent cells that maintain themselves and initiate the formation of lateral organs. After embryonic development, secondary shoot meristems form in the boundary zones between the shoot apical meristem and leaf primordia, the leaf axils. In addition, many plant species develop ectopic meristems at different positions of the plant body. In the compound tomato leaf, ectopic meristems can initiate at the base of leaflets, which are delimited by two distinct boundary zones, referred to as the proximal (PLB) and distal (DLB) leaflet boundaries. We demonstrate that the two leaflet boundaries differ from each other and that ectopic meristem formation is strictly limited to the DLB. Our data suggest that the DLB harbours a group of pluripotent cells that seems to be the launching pad for meristem formation. Initiation of these meristems is dependent on the activities of the transcriptional regulators Goblet (Gob) and Lateral suppressor (Ls), specifically expressed in the DLB. Gob and Ls act in hierarchical order, because Ls transcript accumulation is dependent on Gob activity, but not vice versa. Ectopic meristem formation at the DLB is also observed in other seed plants, like Cardamine pratensis, indicating that it is part of a widespread developmental program. Ectopic meristem formation leads to an increase in the number of buds, enhances the capacity for survival and opens the route to vegetative propagation.